Architecture Computing and the Second World War From Crystallography to Digital research in Architecture - Rocha, João (2018)
The book, focuses at the interweave path of ideas and social connections that occurred between the British Avant-garde and physicists at the dawn of WWII. It presents a new historical framework of how applied research emerged in the field of the building sciences at the immediate aftermath of the Second World War.It is neither a monograph nor it aim is to give an exhausting historical reading. Rather it depicts aspects of the development of twentieth century architectural theory and practice by the engagement of some significant (British) architectural theoreticians with the British Avant-garde, with the philosophy of the Vienna Circle, with formal logic, and with the appearance of building research bureaus.It demonstrate the seminal importance that the Irish physicist and Crystallographer John Desmond Bernal had in promoting a pioneer agenda in the building sciences and subsequently its fundamental influence in Leslie Martin research thoughts. This context led later to the formation of the first applied research centers in the field of Architecture computing, particularly the Land Use and Built Form Studies Center in Cambridge.This work provides a foundation for additional inquiry into the integration of the history of architecture at the level of the development of computational concepts and techniques within architecture theory and practice. A domain which has yet not been explored and to which this research presents an initial framework.